What is known Today about Nutrition and Microbiota - Paolo, Mainardi; Pasquale, Striano; Michele, Mainardi; Paolo, Carta (International Journal of Nutrition, 2022)
We are experiencing years of profound cultural revolution. New insights into the microbiota upset concepts in physiology, medicine, and nutrition. The role of the microbiota for our health is increasingly evident. We are increasingly certain that our health depends on that of the microbiota, or, rather, on its strength in controlling the physiology of body organs, the mechanisms of repair and protection. It is not so much a pathogen that makes us fall ill, but a reduced ability to protect and repair ourselves from damage produced by pathogens that affect us continually. Current knowledge leads us to a new medicine aimed at curing the microbiota so that it can (come back to) take care of us. In this new medicine, food rediscovers a fundamental role, since it is the best way to communicate with the microbiota, to modulate and strengthen it. And it is curious how the most recent acquisitions bring us back to the past, to an ancient medicine, which we had forgotten after the discovery of drugs, imagined capable of acting on complex pathogenetic mechanisms. By acting, more simply, on the microbiota we can activate powerful endogenous mechanisms, which keep us healthy, when we are, more powerful than any drug we can invent. Now there is nothing left to do but apply the new knowledge.
Keywords: Microbiota; nutrition; taste receptors; new medicine.